Inclusive Development for Marginal Group Street Trader in Tembilahan Indragiri Hilir District - Eko Handrian; Rosmita Rosmita; Lilis Suriani (Jurnal Administrasi Publik, 2023)
Inclusive development lies not only in social aspects, but is extended to environmental aspects. The concept of social exclusion and inclusion has redefined the concept of economic development which must also rely on a social approach or use an inclusive development approach. The presence of street vendors for the economy can have a positive impact, but on the other hand it has a negative impact on urban planning and the environment. This research aims to understand and achieve inclusive development for the marginalized group of street vendors in Tembilahan. This study uses qualitative methods by collecting interview data, observation and documentation as well as data analysis by presenting data, reducing and drawing conclusions. The results show that there is no inclusive development for marginalized groups of street vendors in Tembilahan as seen by the minimal participation in development. Participation only occurs when there is control and arrangement for street vendors, then there is no policy that specifically regulates street vendors, besides that the difference in formalization and provision of space in the arrangement among street vendors, from all these findings the impact is not inclusive and comprehensive in the development of marginal groups of street vendors.